2011
DOI: 10.1002/app.33888
|View full text |Cite
|
Sign up to set email alerts
|

Thermal destruction of carbon black network structure in natural rubber vulcanizate

Abstract: To investigate thermal destruction and rearrangement of the carbon black (CB) network consisting of CB aggregates in rubbery matrix, the proper heat-treatment temperature without thermal decomposition of rubber matrix were examined by using differential scanning calorimetry, dynamic mechanical measurements, and thermal expansion measurements. 383 K was chosen as the heat-treatment temperature under vacuum. The volume resistivity (q v ) of 50 phr CB-filled natural rubber vulcanizate (CB-50) increased rapidly up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 78 publications
0
8
0
Order By: Relevance
“…Meanwhile, on the basis of q v measurements and 3D TEM observations, Kato et al14 reported that the CB net in CB‐filled crosslinked NR was destroyed when the heat treatment conditions were set to minimize the occurrence of thermal oxidative degradation. It was found that the crosslinked chains of the CB net were broken by the heat treatment process and that the number of branched chains increased.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, on the basis of q v measurements and 3D TEM observations, Kato et al14 reported that the CB net in CB‐filled crosslinked NR was destroyed when the heat treatment conditions were set to minimize the occurrence of thermal oxidative degradation. It was found that the crosslinked chains of the CB net were broken by the heat treatment process and that the number of branched chains increased.…”
Section: Introductionmentioning
confidence: 99%
“…Since as the surface area of CB increases, the rubber composite exhibited higher Young's moduli, lower tensile strength, and elongation at the break. Kato et al [ 21 ] found that thermal treatment of CB influences the structure and surface area of CB which affects the properties of CB filled rubber composites. Jovanović et al [ 22 ] studied the content of CB effects on the mechanical properties of the NBR/EPDM rubber blend.…”
Section: Introductionmentioning
confidence: 99%
“…Compounding rubber and filler usually rises temperature of compounds due to the friction during mixing and sometimes, the compounds are thermally treated at high temperatures for modifying the physical mechanical properties . Thermal‐treatment influences the performance of rubber compounds intricately while the exact mechanisms remain ambiguous.…”
Section: Introductionmentioning
confidence: 99%